The First Examples of Lithium‐Containing Mixed‐Alkali Strontium Borates with Different Dimensional Anionic Architectures and Short Cutoff Edges. Issue 57 (10th September 2018) - Ma, Ruru; Yang, Yun; Hu, Cong; Yang, Zhihua; Pan, Shilie
Abstract: Three new mixed‐alkali strontium borates, Li2 KSr6 (BO3 )5, Li2 Rb7 Sr24 (BO3 )19, and Li2 Rb2 SrB18 O30, have been synthesized by the high‐temperature solution method by adjusting the molar ratios of the reactants. They represent the first examples of lithium‐containing mixed‐alkali strontium borates. The structures of the three compounds show different dimensional anionic architectures, with Li2 KSr6 (BO3 )5 and Li2 Rb7 Sr24 (BO3 )19 possessing isolated BO3 units, whereas Li2 Rb2 SrB18 O30 has three‐dimensional (3D) ∞ 3 [ B 9 O 15 ] 3 - open frameworks with three types of channels occupied by the strontium and rubidium atoms. Interestingly, Li2 KSr6 (BO3 )5 is the first example of a ∞ 1 [ Li 2 O 7 ] 12 - chain composed of LiO5 linked through the sharing of vertexes and edges. However, in Li2 Rb7 Sr24 (BO3 )19, isolated LiO3 units can be observed, which is also rare in borates. Detailed analysis and comparisons of the structures of the anhydrous mixed‐alkali‐ and alkaline‐earth‐metal borates and nine‐polymeric fundamental building blocks have been made. Furthermore, Li2 Rb7 Sr24 (BO3 )19 and Li2 Rb2 SrB18 O30 present short cutoff edges (<190 nm), which was confirmed by the UV/Vis/NIR diffuse reflectance spectra. These attributes make them attractive for deep‐UV optical materials. Abstract : Interesting boron ! The first examples of lithium‐containing mixed‐alkali strontium borates, Li2 KSr6 (BO3 )5, Li2 Rb7 Sr24 (BO3 )19, and Li2 Rb2 SrB18 O30, have been prepared and characterized. The three compounds show different dimensional anionic architectures. Li2 KSr6 (BO3 )5 and Li2 Rb7 Sr24 (BO3 )19 have isolated BO3 units, and Li2 Rb2 SrB18 O30 features a 3D [B9 O15 ] 3− anionic framework containing three types of channels (see figure). All compounds show short cutoff edges (<190 nm).